2019
DOI: 10.1097/md.0000000000015530
|View full text |Cite
|
Sign up to set email alerts
|

Short- and long-term impacts of adenoidectomy with/without tonsillectomy on immune function of young children <3 years of age

Abstract: To investigate the short- and long-term impacts of adenoidectomy with/without tonsillectomy on the immune functions of young children < 3 years of age. This longitudinal prospective study included 40 pediatric patients (age <3 y) undergoing adenoidectomy with/without tonsillectomy for snoring and sleep apnea. Serum immunoglobulin IgA, IgG, IgM, complement C3, and C4 levels were measured for the status of humoral immunity; CD3+, CD4+, CD8+, CD4+/CD8+, CD19+, CD56+, CD3+CD4-CD8-, and CD3+CD4+CD8+ T ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 26 publications
(27 reference statements)
0
11
0
Order By: Relevance
“…Furthermore, Yan et al reported that adenoidectomy with/without tonsillectomy in children less than 3 years of age does not lead to negative impacts on the immune system. 16 However, clinicians should inform the complications of tonsillectomy such as bleeding, pain, taste disorders, tooth damage, and residual tonsils to patients. The criteria for tonsillectomy should therefore be limited to severe cases that have sustained proteinuria of more than 0.3 g/day after multiple-drug therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Yan et al reported that adenoidectomy with/without tonsillectomy in children less than 3 years of age does not lead to negative impacts on the immune system. 16 However, clinicians should inform the complications of tonsillectomy such as bleeding, pain, taste disorders, tooth damage, and residual tonsils to patients. The criteria for tonsillectomy should therefore be limited to severe cases that have sustained proteinuria of more than 0.3 g/day after multiple-drug therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Tonsil tissue, as a vital part of the Waldeyer ring, is an important component of the immune system located centrally at the entrance of respiratory and gastrointestinal systems, where pathogens, infectious agents, and allergens invading the upper respiratory tract rst encounter the immune system [1]. Tonsil tissue is a secondary lymphoid organ that exerts both humoral and cellular immunity functions against various antigens with speci c antibodies, B and T cell activities, and protects the body especially in young children [2]. Hence, in patients with tonsillitis, cellular, and humoral immune responses are stimulated together.…”
Section: Introductionmentioning
confidence: 99%
“…Hypertrophy may also occur following bouts of local or systemic infection. However, they may also undergo atrophy with chronic disease processes [2].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies with small sample sizes found that the initial immunological deficit following tonsillectomy in children becomes normal after 1 month [ 18 ], 6 months [ 19 ], and 54 months [ 20 ]. Similarly, a recent study concluded that the examined humoral and cellular immunity markers were not altered by adenoidectomy with/without tonsillectomy in children, nor did the surgery lead to an increased risk of infection, nor to immune-deficiency disorders in the 3 months following the operation [ 21 ].…”
mentioning
confidence: 99%